Rancang Bangun Exhaust System pada Skuter Roda Tiga Minimalis - Syahrial Virdan Ichwanushofa; Mohamad Hakam; Tri Andi Setiawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2021)
Commercial vehicles are considered to be able to facilitate the logistics process, for example three-wheeled commercial vehicles, but on the other hand the less affordable prices make people spin their brains to modify makeshift vehicles to be used as commercial vehicles by ignoring safety, security, or comfort. Therefore, a minimalist three-wheeled scooter was created to reduce prices but not reduce safety, features, and comfort for the rider or those around him so that they can compete with products in their class. In this final project the author focuses on designing an optimal exhaust system for a minimalist three-wheeled scooter. The exhaust system serves to reduce exhaust noise from the engine and affect the comfort of the rider and those around him. With the Ulrich method, a suitable concept for a three-wheeled scooter will be selected. Based on the results of the calculation and design process on the exhaust system, the dimensions of the exhaust system channel are 433.25 mm x 98.85 mm x 95.13 mm and the muffler is 360 mm x 76.2 mm x 76.2 mm. Fluid flow analysis shows a back pressure of 15.62 Pa in the exhaust system line and 88.17 Pa in the muffler. Noise testing is carried out on the exhaust system and has met the standards of the Ministry of Environment and Forestry of the Republic of Indonesia with the highest test result of 75.2 dB with a standard of 83 dB.